2021
DOI: 10.1111/psyp.13778
|View full text |Cite
|
Sign up to set email alerts
|

Left‐hemispheric predominance on appropriateness evaluation of restructuring during chunk decomposition problem solving

Abstract: Restructuring refers to achieving satisfactory solutions by breaking obstacles or forming novel associations in problem‐solving. One critical question arises regarding how an appropriate solution is processed in our brain during the restructuring of problem representations. This study aims to explore the electrophysiological correlates of appropriateness evaluation of restructuring by employing a chunk decomposition task. During loose or tight chunk decomposition, participants needed to assess whether they cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 63 publications
5
17
0
Order By: Relevance
“…In the 300–800 ms time windows, novel ideas elicited greater positive waves than ordinary ideas in the posterior scalp, whereas in 800–2000 ms time windows, novel ideas elicited greater negative waves in the posterior scalp than ordinary ideas, and inappropriate ideas also elicited greater negative waves than ordinary ideas, which was likely related to the complex processing in conceptual understanding. The observed LPC/LNC over the parietal scalp was similar to several other studies that adopted the same character decomposition task (Zhang et al, 2019, 2020, 2021), and in line with previous fMRI studies, in which the novel path of chunk decomposition was found to recruit less activation of the primary visual cortex but greater activation of the secondary visual cortex and parietal regions than the ordinary pathway, which was suggested to reflect the inhibition of the automatic chunking effect and the reconstruction of spatial representation (Huang, Zhao, et al, 2019; Huang, Han, et al, 2019; Luo & Knoblich, 2007; Wu et al, 2013). When greater difficulties occurred in manipulating spatial representations, increased activation of the prefrontal and parietal cortices was observed (Tang et al, 2016); both the novelty and (in)appropriateness factors of chunk decomposition influenced the processing difficulties and the activation in the prefrontal and parietal cortices (Huang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…In the 300–800 ms time windows, novel ideas elicited greater positive waves than ordinary ideas in the posterior scalp, whereas in 800–2000 ms time windows, novel ideas elicited greater negative waves in the posterior scalp than ordinary ideas, and inappropriate ideas also elicited greater negative waves than ordinary ideas, which was likely related to the complex processing in conceptual understanding. The observed LPC/LNC over the parietal scalp was similar to several other studies that adopted the same character decomposition task (Zhang et al, 2019, 2020, 2021), and in line with previous fMRI studies, in which the novel path of chunk decomposition was found to recruit less activation of the primary visual cortex but greater activation of the secondary visual cortex and parietal regions than the ordinary pathway, which was suggested to reflect the inhibition of the automatic chunking effect and the reconstruction of spatial representation (Huang, Zhao, et al, 2019; Huang, Han, et al, 2019; Luo & Knoblich, 2007; Wu et al, 2013). When greater difficulties occurred in manipulating spatial representations, increased activation of the prefrontal and parietal cortices was observed (Tang et al, 2016); both the novelty and (in)appropriateness factors of chunk decomposition influenced the processing difficulties and the activation in the prefrontal and parietal cortices (Huang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Tasks involving cognitive control generally exhibited the LSP effect followed by the N2 and N400, which was suggested to be associated with the resolution of the monitored conflicts (Donohue et al, 2016; Feroz et al, 2017; Heidlmayr et al, 2020; Kropotov et al, 2017). Specifically, in previous studies that focused on successful insight‐like problem solving, the LSP following the N2‐ or N400‐like component was suggested to reflect applying complex operations to original ideas and forming novel associations, particularly when the original ideas were directly provided to participants (Li et al, 2013; Li et al, 2020; Mai et al, 2004; Zhang et al, 2019, 2020, 2021; Zhao et al, 2014; Zhou et al, 2018). In independent insight‐like problem solving, due to the large differences in the influence of predominant ordinary ideas and subordinate original ideas, participants are unlikely to find the right solution in a short time and are thus very likely to inhibit the predominant ideas or blindly explore alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis epoch for the ERP was 2200 ms and was time-locked to the problem onset, including a 200ms prestimulus baseline. As previous studies showed that greater N2, N400 and late sustained potentials (LSP) were found when solving creative or insight-like problems than ordinary problems (Abraham et al, 2021;Kroger et al, 2013;Li et al, 2020;Rataj, Przekoracka-Krawczyk, & van der Lubbe, 2018), we measured the mean amplitude of these components at 280-380 ms, 380-600 ms, and 600-1000 ms, respectively, referring to the classic time windows analyzed for conflict monitoring and resolutionrelated components (Heidlmayr et al, 2020) and the observed windows of these components in Chinese character decomposition tasks (Tang et al, 2022;Zhang et al, 2019Zhang et al, , 2020Zhang et al, , 2021.…”
Section: Eeg Recording and Erp Analysismentioning
confidence: 99%
“…For example, in a creative/insightful chunk decomposition task, individuals judged whether the solution was a valid character (appropriate) or pseudocharacter (inappropriate) after removing a target from a source character. Novelty (novel vs. ordinary) was manipulated by whether chunk decomposition occurred at stroke or radical levels (Tang et al, 2022), or at intersecting or nonintersecting levels (Zhang et al, 2021). Behaviorally, both studies found lower judgment accuracy and longer reaction times in the novel (vs. common) condition.…”
Section: The Critical Yet Undifferentiated Role Of Appropriatenessmentioning
confidence: 99%
“…Specifically, the neural mechanisms underlying this process require further clarification, as there are certain limitations in the methodologies and experimental designs employed thus far. One such limitation is that the chunk decomposition approach, which assesses creativity based on whether it results in a real or pseudo-character (e.g., Tang et al, 2022; Zhang et al, 2021), may not accurately reflect the appropriateness of novel solutions. It is possible for individuals to arrive at an “appropriate” solution through chunk decomposition, even if it is a pseudo-character.…”
Section: The Critical Yet Undifferentiated Role Of Appropriatenessmentioning
confidence: 99%